Designing Magnetic Semiconductors From a Ferromagnetic Metallic Glass - Wang, Xinchao; Li, Xuan; Chen, Na; Zhang, Tao (Frontiers in Materials, 2022)
Utilizing both charge and spin degrees of freedom of electrons simultaneously in magnetic semiconductors promises new device concepts by creating an opportunity to realize data processing, transportation and storage in one single spintronic device. Unlike most of the traditional diluted magnetic semiconductors, which obtain intrinsic ferromagnetism by adding magnetic elements to non-magnetic semiconductors, we attempt to develop new magnetic semiconductors via a metal-semiconductor transition by introducing oxygen into a ferromagnetic Co-Fe-B metallic glass. The atomic structure and electronic structure of the Co-Fe-B-O sample are explored by using first-principles calculations. The total pair correlation functions of both the Co-Fe-B and Co-Fe-B-O samples evidence their glass structures. The bond pair and coordination number analysis together demonstrate that the oxygen addition enables the bond types to change from the dominant metallic bonding of the Co-Fe-B metallic glass to the mixture of metallic, ionic and covalent bonding of the Co-Fe-B-O oxide glass. This results in the localization of electron charge density and the opening of the band gap in the Co-Fe-B-O oxide glass. The density of states suggests the Co-Fe-B-O oxide glass is semiconducting with a band gap of about 1.7 eV, but there are intermediate energy levels in the band gap. Meanwhile, the Co-Fe-B-O oxide glass remains to be ferromagnetic. These results show the Co-Fe-B-O oxide glass is a magnetic semiconductor transferred from a ferromagnetic Co-Fe-B metallic glass, which is further verified by the experimental realization of a Co-Fe-B-O magnetic semiconductor. Furthermore, our calculation results reveal that a hybridization of the 4s/4p, 3d electrons of ferromagnetic Co and Fe atoms and O 2p electrons occurs. Such s, p-d exchange interaction is essential to bridge the mutual interaction between the electrical conduction arising from s-like electrons and ferromagnetism supported by 3d electrons in magnetic semiconductors, thereby enabling the control of ferromagnetism by electrical means. Our calculation results represent an important step to gain a deeper understanding of the oxygen addition induced metal-semiconductor transition in an amorphous alloy Co-Fe-B system. We anticipate that our calculation results provide theoretical fundamentals for experimentally transferring many other ferromagnetic amorphous alloys into ferromagnetic semiconductors with attractive magnetoelectric coupling properties.